Comparative effectiveness of all levels miniplate fixation versus a modified hybrid fixation in cervical expansive open-door laminoplasty. Issue 38 (September 2019) - Yang, Zechuan; Liu, Chaoxu; Lin, Yang; Hu, Weihua; Chen, Wenjian; Li, Feng; Zeng, Heng
Abstract : Abstract: In this study, we first reported of a modified hybrid fixation method in expansive open-door laminoplasty (EOLP) in order to reduce medical costs. The purpose of the present study is to compare the surgical outcomes and cost-effectiveness of the modified fixation with all levels miniplate fixation in EOLP for multilevel cervical spondylotic myelopathy. Data of 67 patients who underwent EOLP from July 2015 to June 2016 were retrospectively analyzed, with 33 in the modified group and 34 in the all miniplate group based on their surgical approaches. Laminae were kept open with alternate levels miniplate and anchor fixation in the modified group, while with all levels miniplate fixation in the all miniplate group. Medical costs and clinical results including Japanese Orthopedic Association (JOA) scores, Visual Analogue Scale (VAS) scores and occurrences of complications were investigated and compared between the 2 groups. After evaluation on X-ray, CT, and MRI, radiographic data reflecting cervical alignments, spinal canal enlargement and spinal cord decompression were collected and compared within each group and between the 2 groups. After a follow-up period of about 18 months, no significant differences in operation time, intraoperative blood loss, complication rates, VAS scores, neurological recovery rates and postoperative hospital stays were observed between the 2 groups. However, EOLP with the modified fixation costed less. When comparing the 2 groups, cervical curvature index (CCIs) which reflected cervical alignments and anteroposterior diameters (APDs) reflecting spinal canal enlargement at all the follow-ups had no significant differences. Postoperative open angles which reflected spinal cord decompression of C4 and C6 were significantly smaller in the modified group. However, that difference was no longer detected at the final follow-up. Within each group, APDs increased significantly after surgery. However, no significant differences in CCIs and open angles at different follow-ups were observed in each group. Compared with all miniplate fixation, the modified hybrid fixation in EOLP showed almost the same clinical and radiographic results. However, the modified hybrid fixation method could reduce costs.